2004
DOI: 10.1097/01.asn.0000125614.35046.10
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tubular Hypoxia in the Early Phase in the Remnant Kidney Model

Abstract: Abstract. The remnant kidney model is a mainstay in the study of progressive renal disease. The earliest changes in this model result from glomerular hemodynamic alterations. Given that progressive renal disease is the result of subsequent interstitial damage initiated by undetermined pathogenic factors, the authors investigated the role of hypoxia as a pathogenic factor in tubulointerstitial damage after renal ablation in rats. Cortical tissue hypoxia in the early phase (4 and 7 d) in remnant kidney rats, sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
183
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 47 publications
8
183
0
Order By: Relevance
“…The remnant kidney is a disease model classically characterized by glomerular and systemic hypertension, but a recent study highlighted potential significance of hypoxia, which was observed at a very early stage in this condition. 17 In the present study, we demonstrated that cobalt mediated significant improvement in tubulointerstitial injury as well as preservation of glomerular and peritubular capillary networks with no evidence of vascular leakage. Underlying mechanisms included proliferation of microvascular endothelial cells and reduced numbers of apoptotic tubular cells.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The remnant kidney is a disease model classically characterized by glomerular and systemic hypertension, but a recent study highlighted potential significance of hypoxia, which was observed at a very early stage in this condition. 17 In the present study, we demonstrated that cobalt mediated significant improvement in tubulointerstitial injury as well as preservation of glomerular and peritubular capillary networks with no evidence of vascular leakage. Underlying mechanisms included proliferation of microvascular endothelial cells and reduced numbers of apoptotic tubular cells.…”
mentioning
confidence: 54%
“…17 However, some controversy remains as to whether hypoxia is still present in the advanced stages of this model. 28,29 In this regard, pimonidazole staining was conducted to visualize hypoxia at week 9 of the remnant kidney ( Figure 1).…”
Section: Tubulointerstitial Hypoxia In the Remnant Kidneymentioning
confidence: 99%
“…There are, in fact, cases in which tubulointerstitial hypoxia even precedes injury in some immune-and nonimmune-mediated glomerulopathies. 45,46 The findings of such studies may potentially extend the current prevalent view of hypoxia from that of a modulator of tubulointerstitial injury to a possible trigger of it.…”
Section: Discussionmentioning
confidence: 93%
“…[37][38][39] ARBs, particularly telmisartan and olmesartan, also exert antidiabetic effects through their regulation of insulin sensitivity and reduce not only urinary albumin excretion but also urinary 8-OHdG and L-FABP excretion. 40 Statins have been shown to ameliorate tubular and podocyte injury, preserve GFR and reduce proteinuria in renal disease.…”
Section: Discussionmentioning
confidence: 99%